2007
DOI: 10.1016/j.cell.2007.10.004
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental Origin of Fat: Tracking Obesity to Its Source

Abstract: The development of obesity not only depends on the balance between food intake and caloric utilization but also on the balance between white adipose tissue, which is the primary site of energy storage, and brown adipose tissue, which is specialized for energy expenditure. In addition, some sites of white fat storage in the body are more closely linked than others to the metabolic complications of obesity, such as diabetes. In this Review, we consider how the developmental origins of fat contribute to its physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
826
0
18

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,269 publications
(893 citation statements)
references
References 104 publications
17
826
0
18
Order By: Relevance
“…Triacylglycerols stored in the white adipose tissue serve as the major energy reserve in higher eukaryotes (1). Although they are constantly turned over by lipolysis and re-esterification, their mobilization and storage are precisely balanced by various hormones and other factors depending on the nutritional state (2).…”
Section: Gpr109b Is Coupled To G I -Type G-proteins and Is Activated mentioning
confidence: 99%
“…Triacylglycerols stored in the white adipose tissue serve as the major energy reserve in higher eukaryotes (1). Although they are constantly turned over by lipolysis and re-esterification, their mobilization and storage are precisely balanced by various hormones and other factors depending on the nutritional state (2).…”
Section: Gpr109b Is Coupled To G I -Type G-proteins and Is Activated mentioning
confidence: 99%
“…3 During the development of adipose tissue, pre-adipocytes or precursor/stem cells differentiate into mature adipocytes through complex adipogenic programs that regulate signaling transduction, transcriptional regulation, cell cycle and mitochondrial metabolism. [5][6][7][8][9][10] The transcription factor forkhead box O1 (FoxO1) regulates an array of genes and integrates insulin signaling with metabolic homeostasis, which has been shown to play an important role in adipogenesis. 5,[11][12][13][14][15] In particular, FoxO1 controls adipogenesis through interacting with peroxisome proliferator-activated receptor gamma (PPARg) and the cell cycle inhibitor p21 (CDKN1A).…”
Section: Introductionmentioning
confidence: 99%
“…7 Like muscle and bone, adipose tissue is mesodermal in origin. 9 In mice, adipose tissue development occurs during the first two weeks of neonatal life. 9,10 The observation that developmental exposure to testosterone programed WAT, muscle, and bone suggested a possible effect of testosterone on mesenchymal stem cells.…”
mentioning
confidence: 99%
“…9 In mice, adipose tissue development occurs during the first two weeks of neonatal life. 9,10 The observation that developmental exposure to testosterone programed WAT, muscle, and bone suggested a possible effect of testosterone on mesenchymal stem cells. Indeed, we observed that in NTF, expression of developmental genes involved in depot-specific identity was altered in SC adipose tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation